An areal typology of clause-final negation in Africa - (:unkn) unknown (My University, 2018)
Clause-final negation markers (CFNMs), although typologically rare, can be found in a very wide range of languages of Northern Sub-Saharan Africa. Based on a sample of 618 African languages, this paper provides an analysis of spatio-temporal language dynamics in Sub-Saharan Africa with respect to the feature CFNM. I argue that it is important to consider together both the languages that have the feature under investigation and the languages that do not have it. Furthermore, in order to better capture the diversity of the languages that have CFNMs, I increase the degree of granularity of my data by taking into account two parameters, viz., obligatoriness of CFNMs and possible restrictions on the freedom to use CFNMs in different constructions. For spatial analysis and visualiza-tion, I use the methods of spatial interpolation and generalized additive model-ing. Both methods converge on the need to distinguish two focal areas of the feature CFNM. The first one, the Central Focal Area, is the most prominent of the two and spans the east of West Africa and parts of Central Africa. The second one, the Western Focal Area, is less prominent and is restricted to West Africa. The two focal areas are separated by a major discontinuity around Ghana, Togo and Be-nin. In order to better calibrate the results of the spatial analysis and to identify the historical core of the Central Focal Area, I call onto other types of data available. Finally, I address the distribution of optional and/or restricted CFNMs in Africa, with a particular focus on the spread of CFNMs among Bantu languages to the south of the Central Focal Area, primarily in the Congo River corridor and the north of the Democratic Republic of Congo.
Keywords: African Research